Structure and annual increase in a population of West Greenland caribou (Rangifer tarandus groenlandicus) - Thing, Henning (Rangifer, 1982)
During 1977-80 a large scale research program was carried out in West Greenland to study caribou ecology and population dynamics. Papers dealing with feeding ecology, range condition, calf mortality, and behaviour have been published elsewhere (Strandgaard 1980; Holt 1980; Clausen et al. 1980; Thing & Clausen 1980; Thing 1980; Roby 1980; Thing 1981; Roby & Thing 1982; Thing & Thing 1982). The present study deals with some dynamic parameters in the Sisimiut herd (Fig. 1), viz. group size, sex and age composition, calf/cow ratio, calf increment, and annual recruitment. Caribou in the Sisimiut region are mainly found in very small groups of one to five animals in most seasons. Aggregations of more than 50 animals are rarely seen except in the calving and summer seasons (Fig. 2). A distinct annual cycle is apparent in the mean group size with a steady increase from a mid winter minimum of 1.4 caribou/group towards a maximum of almost 25 caribou/group in the post-calving season (Fig. 3). The absence of important predators (especially wolves) and the fact that winter food resources in the region have been depleted seem to reduce group size. Consequently, Sisimiut caribou are characterized year round by forming very small groups as compared to most other wild Rangifer populations. Caribou cows (females 2 years + ) make up approx. 50% of the herd, while bulls (males 2 years + ) average only 10% (Fig. 4). The number of bulls in the herd shows a significant decline caused by a selective hunting pressure as well as natural winter mortality (Fig. 5). The rut takes place in October during the fall migration from the inland ranges adjacent to the Inland Ice towards the coast line. The cows are apparently served mainly by 1 1/2 and 2 year old bulls. Despite scarcity of adequate food on the winter ranges there is a high calf production. This is probably explained by excellent forage conditions on the inland range prior to and during the calving season (May - June). Calving adds as much as 40% new individuals to the herd, but following their two first months of life calf numbers were reduced to only 17 - 18% of the population (Fig. 6). This drastic die-off is mainly caused by an epidemical Escherischia coli arthritis. The mean calf mortality from September through May is only about 2 - 3% (Fig. 7), and consequently the annual recruitment averages 15%. Considering the average mortality rates of the other age classes in the population (approx. 7%) the herd increment at the start of the hunting season (August) amounts to only 10%. Mortality in the first year of life (60%) is comparable to that of a broad spectrum of other wild Rangifer populations in northern regions (Fig. 7). However, in the Sisimiut herd reduction of calf numbers almost exclusively takes place during the first three months after birth, while in the other Rangifer populations calf mortality is more evenly distributed throughout the whole year. Struktur og årlig tilvækst i en bestand af vestgønlandsk vildren (Rangifer tarandus groenlandicus). Abstract in Danish / Sammendrag: Som et led i en større økologisk undersøgelse af den vestgrønlandske vildren (Rangifer tarandus groenlandicus) er bestanden i Sisimiut-området (ca. 67 gr N) blevet studeret med hensyn til køns- og aldersstruktur, flokstørrelse, kalv-simle forhold og kalvetilvækst. Sisimiut-bestanden tæller mellem 2500 og 3000 dyr, og består det meste af året hovedsagelig af ganske små flokke på op til 5 dyr. Koncentrationer på flere hundrede dyr ses kun i sommertiden i forbindelse med insektforstyrrelser. Der er en tydelig årsrytme i gennemsnitsstørrelsen af flokkene, således at der sker en jævn stigning fra midvinterens 1,4 dyr pr. flok til et højdepunkt i efter-kælvningstiden med knap 25 dyr pr. flok. Manglen på ulve samt de dårlige, nedslidte føderessourcer i området gør, at dyrene på alle årstider har en meget lille flokstørrelse sammenlignet med andre landes vildrenbestande. Omkring 50% af bestanden udgøres af simler (2 år+), medens 2-årige og ældre bukke kun udgør 10%. Bukkenes andel i bestanden viser en klar nedgang forårsaget af selektiv jagt og naturlig vinterdødelighed. Brunsten finder sted lige efter dyrenes efterårstræk fra indlandets sommergræsgange ud mod de kystnære vinterområder. Trods marginale fødemuligheder på vintergræsgangene er der en stor kalveproduktion. Dette skyldes sandsynligvis de meget gode beiteforhold, der stadigvæk findes på indlandsområdet i tiden før kælvningen og gennem hele sommerperioden. Ved kælvningen i juni tilføres bestanden op til 40% nye individer, men efter de første to levemåneder er kalvenes andel faldet til 17 - 18%. Den store tilbagegang skyldes især en epidemisk ledbetændelse forsaget af E. coli bakterier. Kalvedødeligheden fra september til maj er kun omkring 2 - 3%, således at den årlige gennemsnitlige rekruttering ligger på ca. 15%. Når der tages højde for de øvrige aldersklassers gennemsnitlige dødelighed udgør bestandstilvæksten ved jagtsæsonens start i august blot 10%. Dødeligheden i det første leveår er af samme størrelse (60%) som hos et bredt udsnit af vildrenbestande i andre nordlige områder (Fig. 7). Imidlertid sker reduktionen blandt Sisimiut-bestandens kalve nesten udelukkende i løbet af de første tre måneder efter fødselen, medens kalvedødeligheden i de andre vildrenbestande er mere jævnt fordelt over alle tolv måneder. Kokoonpano ja vuotuinen kasvu lansi-gronlantilaisessa peurakannassa. Abstract in Finnish / Yhteenveto: Yhtena osana suuremmasta ekologisesta tutkimuksesta lansi-gronlantilaisesta peurasta (Rangifer tarandus groenlandicus) on Sisimiut-alueella (n. 67° P) oleva kanta, jota on tutkittu sukupuoli - ja ikajakoon, tokkasuuruuteen, vasikka - vaadin suhteeseen ja vasikkakasvuun nahden. Sisimiut-kanta lasketaan olevan lukumaaraltaan 2500 ja 3000 elaimen valilla, ja se muodostuu suurimmalta osalta vuotta paaasiallisesti aivan pienista partioista - jopa 5 elainta kussakin. Useiden satojen elainten ryhmittymia nahdaan vain kesaaikana hyttyshairioiden yhteydessa. On selva vuosittaisrytmi keskiokokoisissa tokissa siten, etta niissa tapahtuu tasaista nousua keskitalvella 1,4 elainta tokkaa kohti saavuttaen huippupisteen vasomisajan jalkeen tuskin 25 elainta tokkaa kohti. Susien puute seka alueen huonojen loppuunkuluneiden ravintovarojen takia elaimilla kaikkina vuoden aikoina on hyvin pieni laumasuuruus muiden maiden peurakantaan verrattuna. Suunnilleen 50% kannasta on vuoneloja ja vuonelovaatimia (2 v +), kun taas 2-vuotiaita ja sita vanhempia uroksia on vain 10%. Uroksien osuus kannassa osoittaa selvaa vahennysta selektiivisen metsastyksen ja luonnollisen talvikuolleisuuden aiheuttamana. Kiima on heti elainten syysvaelluksen jalkeen sisamaan kesalaitumilta rannikkojen laheisia talvialueita kohti. Talvilaidunmaiden rajoitetuista ravintomahdollisuuksista huolimatta on vasominen runsaslukuista. Tama johtuu todennakoisesti erittain hyvista laidunmaista, joita loytyy alinomaa sisamaan alueella ennen vasomisaikaa ja koko kesakauden. Kesakuun vasomisessa kanta lisaantyy uusilla yksiloilla jopa 40%, mutta kahden ensimmaisen elinkuukauden jalkeen on vasojen lukumaara vahentynyt 17 - 18 %. Suuren taantumisen syyna on erikoisesti E. colibakteerien aiheuttama kulkutautimainen niveltulehdus. Vasojen kuolleisuus syyskuusta toukokuuhun on vain noin 2 - 3 %, siten etta vuoisittainen keskimaarainen lisays on n. 15%. Kun siihen otetaan muiden ikaluokkien keskimaaraisen kuolleisuuden ylaraja, tekee kannan lisays metsastyskauden alussa elokuussa ainoastaan 10%. Ensimmaisena elinvuotena on kuolleisuus samaa suuruutta (60%) kuin useimmilla peurakannoilla muilla pohjoisilla alueilla (Kuv. 7). Kuitenkin Sisimiut-kannassa vasojen vahentyminen tapahtuu melkein yksinomaa kolmen ensimmaisen kuukauden kuluessa vasomisen jalkeen, kun taas vasakuolleisuus muissa peurakannoissa on tasaisemmin jakautunut kaikkien kahdentoista kuukauden osalle.